PENGUKURAN KELELAHAN PEKERJA PEMANEN SAWIT DI DESA TAMBUSAI - Rusrial, Rusrial; Pratama, Bayu Rizki; Satria, Sardi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2020)
Work fatigue is part of a common problem that is often encountered in the workforce. Fatigue in unsolved workers can have a negative effect, both for work and individual workers so that the problem of work fatigue should receive special attention. The physical activities of permanent palm oil work in Kampar, which are all still done manually and are very risky to experience work fatigue. This research is an analytical study that aims to determine the relationship between the characteristics of workers and how they work with work fatigue due to fatigue harvesters conducted by oil palm harvesters in Kampar. There is a relationship between age with work fatigue and between the history of the disease that is harvested by harvesters. From the results of the study it is suggested to those who have oil palm plantations to adjust the number of harvesters by harvesting at different ages of the crop, given the different difficulty levels and burdens of giving money to substitute food and extra pudding as an effort to fulfill workers’ nutrition should not be done. Where nutrition is one of the factors that can affect harvesters fatigue.